Technique development of PC104 embedded module and its application in the geophysical instrument design - Teng, Yun-tian; Zhang, Lian; Wang, Yan; Liu, Xiao-qin; Ma, Yan-ni (Acta seismologica sinica, 2002)
The mainstream embedded resolutions widely adopted in the geophysical observation device are discussed in this paper. The advantages and its applicability of the PC104 embedded module are demonstrated through its performance description, technique development and its applications in the design of the fluxgate magnetometer, the movable seismograph and the GPS steering device.